Analysis of Policy and Politics in Education on Phacoemulsification Training for Newly Graduated Ophthalmologists - Lumapow, Harold R; Sumanti, Eugeni; Surbakti, Salam; Hartonoi, Yuliana; Kasih, Franky; Umboh, Anne (International Journal of Information Technology and Education, 2025)
The increasing burden of cataract-induced blindness in Indonesia demands competent surgical responses, particularly through the phacoemulsification technique—a minimally invasive surgical procedure globally recognized as the gold standard. However, structural limitations in training policies, unequal access to resources, and political dynamics impede the readiness of new ophthalmologists in mastering this technique. This study explores the systemic, policy, and political contexts underlying phacoemulsification training in Indonesia. Using a qualitative descriptive approach supplemented by a literature review, this research analyzes dimensions of curriculum development, accreditation standards, infrastructure distribution, stakeholder politics, and professional ethics compliance. Findings indicate that to ensure equitable surgical competence among graduates of ophthalmology specialist programs, policymakers need to integrate national regulations with international standards, decentralize access to quality training, and enforce ethical governance across all medical education institutions.